Missing IUD Despite Threads at the Cervix - Andrew L. Atkinson; Jonathan D. Baum (Case Reports in Obstetrics and Gynecology)
Today, the intrauterine device (IUD) is by far the most popular form of long term reversible contraception in the world. Side effects from the IUD are minimal and complications are rare. Uterine perforation and migration of the IUD outside the uterine cavity are the most serious complications. Physician visualization and/or the patient feeling retrieval threads at the cervical os are confirmation that the IUD has not been expelled or migrated. We present a case of a perforated, intraperitoneal IUD with threads noted at the cervical os. Office removal was not possible using gentle traction on the threads. Multiple imaging and endoscopic modalities were used to try and locate the IUD including pelvic ultrasound, diagnostic hysteroscopy, cystoscopy, and pelvic magnetic resonance imaging (MRI). The studies gave conflicting results on location of the IUD. Ultimately, the missing IUD was removed via laparoscopy.